The Development of Learning Inquiry Model to Improve Students’ Hots (Higher Order Thinking Skills) during The Covid 19 Pandemic - Muhiddin, Amir; Mustari, Nuryanti; Syamsidah, Syamsidah (Universitas Negeri Makassar, 2021)
This study aims to determine the stages of developing Inquiry Learning (IL) model learning tools to improve students' Higher Order Thinking Skills (HOTS). In addition, the purpose of this study is to find out the learning tools with the inquiry learning (IL) model that are valid, effective, and practical. The research method used is development research. This development research adopted the modified Thiagarajan, Semmel, and Semmel models. The four stages include define, design, develop, and disseminate. The results showed: 1). The stages of developing learning tools have been conducted using the IL model, which refers to the 4 D model, including defining, designing, developing, and disseminating. The learning tool is valid because it obtains an average score of 3.08 from three experts. The learning tools are practical because the observation' results of the IL Model implementation in the experimental class show that the stages of the model have been implemented perfectly with a percentage of 100%. In the data regarding the practicality of the IL model from the aspect of student activity in learning with IL, the results show that students are actively involved in learning with an average score of 3.40 (high activity). The average score of students taught using the IL model (experimental group) was higher than students in the conventional class (control group). The average score of students in the experimental group was 80.6, while the control group was 74.5. It means that the application of IL can improve students' HOTS thinking skills.